2016
DOI: 10.1080/10749357.2015.1116822
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory deficits after stroke: a scoping review

Abstract: In the past years, there have been increasing research activities focusing on somatosensory symptoms following stroke. However, as compared to the large number of clinical and neuroimaging studies on motor symptoms, the number of studies tracing somatosensory symptoms after stroke and their recovery is rather small. It is an ongoing discussion, to which extent somatosensory deficits after stroke influence patient's long-term outcome in motor and sensory performance and functional independence in activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
148
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 99 publications
4
148
0
9
Order By: Relevance
“…Clinical studies have shown impaired social cognition [59,60], memory deficits [61] and somatosensory deficits [62], which may influence overall functional recovery. Functional recovery is most rapid early after stroke, which is typically considered ≤3 months for humans and ≤1 month for rodents [63].…”
Section: Cells and Significant Increases In Cd4+ T Cells And Cd8+ T mentioning
confidence: 99%
“…Clinical studies have shown impaired social cognition [59,60], memory deficits [61] and somatosensory deficits [62], which may influence overall functional recovery. Functional recovery is most rapid early after stroke, which is typically considered ≤3 months for humans and ≤1 month for rodents [63].…”
Section: Cells and Significant Increases In Cd4+ T Cells And Cd8+ T mentioning
confidence: 99%
“…Somatosensory impairment after stroke has been associated with impaired daily actions and activities, according to clinical and laboratory studies (Borstad & Nichols-Larsen, 2014;Carey et al, 2016;Kessner, Bingel, & Thomalla, 2016;Meyer et al, 2014). Somatosensory loss reduces control of hand movements (Jeannerod, Michel, & Prablanc, 1984) and of the fundamental pinch-grip-lift-and-hold task (Blennerhassett, Matyas, & Carey, 2007) and limits grip force control during object manipulation (Nowak & Hermsdörfer, 2005).…”
mentioning
confidence: 99%
“…Trial Registration Clinicaltrials.gov; Registration ID: NCT02565407; Date of registration: 01/10/2015; URL: https://clinicaltrials.gov/ct2/show/NCT02565407 Background Nearly two-thirds of stroke survivors exhibit forms of somatosensory or proprioceptive dysfunction (1,2).…”
mentioning
confidence: 99%